The regulatory principles, physiological functions, and phase transition of biomolecular condensates - Li, Qingxiang; Jiang, Yan; Chen, Yan (Frontiers in Cell and Developmental Biology, 2026)
Liquid-liquid phase separation (LLPS) is a crucial process that influences the spatial organization of cells. Dysregulation of this process can contribute to serious adverse outcomes, including neurodegenerative diseases, developmental disorders, and impaired immune responses. While various studies have explored how factors like physicochemical properties, molecular structures, and post-translational modifications (PTMs) affect the formation of condensates, current knowledge remains fragmented and lacks a cohesive framework. This review aims to systematically compile the principles regulating LLPS, focusing on the interplay between physico-chemical parameters, PTMs, and molecular sequence characteristics. Building on this foundation, we will also examine the significance of physiological phase separation and its connection to pathological phase transitions, such as the conversion from a liquid to a solid state.